Banking crises and mortality during the Great Depression: evidence from US urban populations, 1929–1937. Issue 5 (24th March 2011) - Stuckler, David; Meissner, Christopher; Fishback, Price; Basu, Sanjay; McKee, Martin
Abstract : Background: Previous research suggests that the Great Depression led to improvements in public health. However, these studies rely on highly aggregated national data (using fewer than 25 data points) and potentially biased measures of the Great Depression. The authors assess the effects of the Great Depression using city-level estimates of US mortality and an underlying measure of economic crisis, bank suspensions, at the state level. Methods: Cause-specific mortalities covering 114 US cities in 36 states between 1929 and 1937 were regressed against bank suspensions and income data from the Federal Deposit Insurance Corporation Database, using dynamic fixed-effects models and adjustments for potential confounding variables. Results: Reductions in all-cause mortalities were mainly attributable to declines in death rates owing to pneumonia (26.4% of total), flu (13.1% of total) and respiratory tuberculosis (11.2% of total), while death rates increased from heart disease (19.4% of total), cancer (8.1% of total) and diabetes (2.9%). Only heart disease can plausibly relate to the contemporaneous economic shocks. The authors found that a higher rate of bank suspensions was significantly associated with higher suicide rates (β=0.32, 95% CI 0.24 to 0.41) but lower death rates from motor-vehicle accidents (β=−0.18, 95% CI −0.29 to −0.07); no significant effects were observed for 30 other causes of death or with a time lag. Conclusion: In contrast with existing research, the authors find that many of the changes in deaths from different causes during the Great Depression were unrelated to economic shocks. Further research is needed to understand the causes of the marked variations in mortality change across cities and states, including the effects of the New Deal and Prohibition.